Музична палітра Національного оркестру - Черкаський, Л. (Народна творчість та етнографія, 2006)
The article under consideration suggests the information on the National Orchestra of Folk Instruments, which celebrates its 35th anniversary. The author describes the repertoire of the concert dedicated to this event brightly. A great part of the work depicts the history of creation of the orchestra, the specific features of the instruments used in it, the peculiarities of the repertoire. Finally, the author speaks of Victor Hutsal, a conductor of the great talent.